Efforts to Implement Cybercrime Offences in Using Social Media - Ahmad Zulqarnain Hasibuan; Syaiful Asmi Hasibuan (International Journal of Law, Crime and Justice, 2024)
Knowing how legal remedies are in the use of social media, social media has become a phenomenal and inseparable need for the Indonesian people. Some of the features possessed by social media include uploading statuses, sharing news pages, chatting, audiovisual communication and other features. Even though all people's behavior on social media platforms has been regulated by law, criminal acts as cybercrime still occur. Cybercrime is an unusual form of crime, in fact this crime can not only harm society, but can cause losses, and the peak can even destroy a country. This information age is often referred to as the digital revolution through technological developments and the development of communication tools. The internet is an information and communication technology that is most often encountered in human activities. The internet is one for surfing in cyberspace without any restrictions, a network that is very easy to access. The Criminal Procedure Code (KUHAP) and the Law on Information and Electronic Transactions (UU ITE), namely Law Number 19 of 2016 Amendments to Law Number 11 of 2008 have been applied to cyber crime.